Analisis Penerapan Komunikasi SBAR dalam Pelaksanaan Handover Perawat di Bangsal Al-Ashr - Meilani, Dina; Kurnia Sari, Novita; Prasetyantoro, Indra (Pustaka Galeri Mandiri, 2026)
Effective communication is a crucial factor in ensuring patient safety, especially during nursing handover. One commonly used communication method is SBAR (Situation, Background, Assessment, Recommendation). This study aimed to analyze the implementation of SBAR communication in nursing handover in the Al-Ashr ward at PKU Muhammadiyah Bantul Hospital. This study used an observational design with a descriptive approach and cross-sectional method. Data were collected using an observation checklist involving 12 nurses with a total of 30 observations conducted from March 23 to April 4, 2026, across morning, afternoon, and night shifts. The results showed that the overall implementation of SBAR communication was mostly optimal (56.7%), while 43.3% was not optimal. Among the components, situation had the highest optimal rate (93.3%), followed by background (90.0%) and assessment (90.0%), while recommendation had the lowest (83.3%). In conclusion, the implementation of SBAR communication in nursing handover was generally good; however, improvements are still needed, especially in the recommendation component to enhance patient safety and continuity of care.